TEARING UP THE DISK: HOW BLACK HOLES ACCRETE - Nixon, Chris; King, Andrew; Price, Daniel; Frank, Juhan (Astrophysical journal. Letters, 2012)
We show that in realistic cases of accretion in active galactic nuclei or stellar-mass X-ray binaries, the Lense-Thirring effect breaks the central regions of tilted accretion disks around spinning black holes into a set of distinct planes with only tenuous flows connecting them. If the original misalignment of the outer disk to the spin axis of the hole is 45[degrees] [<, ~] [straighttheta] [<, ~] 135[degrees], as in ~70% of randomly oriented accretion events, the continued precession of these disks sets up partially counterrotating gas flows. This drives rapid infall as angular momentum is canceled and gas attempts to circularize at smaller radii. Disk breaking close to the black hole leads to direct dynamical accretion, while breaking further out can drive gas down to scales where it can accrete rapidly. For smaller tilt angles breaking can still occur and may lead to other observable phenomena such as quasi-periodic oscillations. For such effects not to appear, the black hole spin must in practice be negligibly small, or be almost precisely aligned with the disk. Qualitatively similar results hold for any accretion disk subject to a forced differential precession, such as an external disk around a misaligned black hole binary.